„Wysmaruję wam twarze gnojówką” (Ml 2,3b). Mowa Boga do kapłanów (Ml 2,1–9) jako manifest reformy Nehemiasza. Kryzys kapłaństwa i degradacja lewitów w pierwszej połowie V wieku przed Chr. - Zawadzki, Arnold (The Biblical Annals, 2023)
The article aims to demonstrate that Mal 2:1–9 is a manifesto of the reform that led to the degradation of the Levites in Nehemiah’s time (mid-fifth century BC), elevating a new generation of priests, who may have been Sadocites or Aaronites, to the chief priesthood (the OT texts are not conclusive here). On the one hand, Julius Wellhausen’s theory, which indicates that the degradation of the Levites was an aftermath of Josiah’s reform, is challenged, while on the other, certain texts (2 Kgs 23:9–10; texts P and Ezek 44:10–16) are interpreted as a post-exile attempt to archaically project the degradation of the Levites to the pre-exile period. An exegetical analysis further reveals that Mal 2:1–9 (together with some Deuteronomistic texts) is the youngest and last historical testimony to the Levites’ priesthood prior to their degradation. A new translation and interpretation enrich the previous understanding of the pericope. It is also plausible that a close associate of Nehemiah or Nehemiah himself is disguised as Malachi.